Socio-spatial Mobility from Pierre Bourdieu’s Theory: Capital of Motility, Field of Mobility and Mobile Habitus - García Jerez, Francisco Adolfo (Sociedad y Economía, 2016)
In the last decades a sociological interest has been raised on means of transportationand in general on ontology of mobility. This interest has been generated, among others,due to technological development which has transformed deeply the means of transportationand, with it, has restructured notions such as space and time as well as the logicsof spatial mobility. We think that in this task, sociology offers enough background andtheoretical and methodological instruments in order to explain these social changes.In this sense, this article would wish to contribute to these debates rising a theoreticalpropose that, from constructivist-structuralism of Pierre Bourdieu, deal with the issue ofsocio-spatial mobility. For that, we have applied the notions of capital of motility, fieldof mobility and mobile habitus.